2007
DOI: 10.1111/j.1540-8167.2007.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Atrial Arrhythmias Detected by Permanent Pacemakers (PPM) Post‐Pulmonary Vein Antrum Isolation (PVAI) for Atrial Fibrillation (AF): Correlation with Symptomatic Recurrence

Abstract: Detection of atrial tachyarrhythmias by a PPM occurred in 30% of patients without symptomatic AF recurrence. Most of these episodes were <60 seconds and waned within 3 months. Sustained, asymptomatic episodes were uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…In our study with regular daily monitoring for one year, only 2% patients did not recognize any AF/AT recurrence and were exposed to wrong clinical judgement on their ablation outcome. This is less than in the abovementioned studies, however, in accord with other studies (utilizing ECG monitoring including monitoring functions of implanted pacemakers) that have observed only 2-3% of entirely asymptomatic patients with post-ablation AF/AT recurrences 17,18 . Disparities in individual symptom perception may largely depend on how the patients were instructed and able to correctly interpret AF-related symptoms other than palpitations, like dyspnoea, fatigue or incapacity.…”
Section: Discussionsupporting
confidence: 78%
“…In our study with regular daily monitoring for one year, only 2% patients did not recognize any AF/AT recurrence and were exposed to wrong clinical judgement on their ablation outcome. This is less than in the abovementioned studies, however, in accord with other studies (utilizing ECG monitoring including monitoring functions of implanted pacemakers) that have observed only 2-3% of entirely asymptomatic patients with post-ablation AF/AT recurrences 17,18 . Disparities in individual symptom perception may largely depend on how the patients were instructed and able to correctly interpret AF-related symptoms other than palpitations, like dyspnoea, fatigue or incapacity.…”
Section: Discussionsupporting
confidence: 78%
“…The results of our study are consistent with those of studies by Purerfellner et al 16 and Verma et al 17. Purerfellner et al evaluated earlier methodologies of catheter ablation for AF in a small number of patients with implantable devices and demonstrated a significant reduction in AF burden after ablation, but continued episodes of both symptomatic and asymptomatic AF were also observed.…”
Section: Discussionsupporting
confidence: 92%
“…One report determined that PPM detected atrial tachyarrhythmia recurrences in 30% of patients without symptoms of AF, and revealed that most of these episodes were <60 s in duration and subsided within 3 months. 16 The second report compared freedom from AF as assessed by patient symptoms (71% of patients after catheter ablation), 24-to 48-h Holter monitor recording every 6 months (64%), 1-week Holter monitor recording every 6 months (58%), and continuous monitoring by the PPM (43%). The authors concluded that the more rigorous the monitoring, the more AF was uncovered.…”
Section: Undetected Af Recurrencementioning
confidence: 99%